Reputation: 118560
The List monad has return x = [x]
. So why in the following example is the result not [(["a", "b"], [2, 3])]
?
> pairs a b = do { x <- a; y <- b; return (x, y)}
> pairs ["a", "b"] [2,3]
[("a",2),("a",3),("b",2),("b",3)]
Upvotes: 2
Views: 194
Reputation: 71074
In general,
pairs a b = do { x <- a; y <- b; return (x, y) }
= do { x <- a;
do { y <- b;
do { return (x, y) }}}
means, in pseudocode,
pairs( a, b) { for x in a do:
for y in b do:
yield( (x, y) );
}
whatever the "for ... in ... do"
and "yield"
mean for the particular monad. More formally, it's
= a >>= (\x ->
do { y <- b; -- a >>= k ===
do { return (x, y) }}) -- join (k <$> a)
= join ( (<$> a) -- ( a :: m a
(\x -> -- k :: a -> m b
do { y <- b; -- k <$> a :: m (m b) )
do { return (x, y) }}) ) -- :: m b
( (<$>)
is an alias for fmap
).
For the Identity
monad, where return a = Identity a
and join (Identity (Identity a)) = Identity a
, it is indeed
pairs( {Identity, a}, {Identity, b}) { x = a;
y = b;
yield( {Identity, {Pair, x, y}} );
}
For the list monad though, "for"
means foreach
, because return x = [x]
and join xs = concat xs
:
-- join :: m (m a) -> m a
-- join :: [] ([] a) -> [] a
-- join :: [[a]] -> [a]
join = concat
and so,
join [ [a1, a2, a3, ...],
[b1, b2, b3, ...],
.....
[z1, z2, z3, ...] ]
=
[ a1, a2, a3, ... ,
b1, b2, b3, ... ,
.....
z1, z2, z3, ... ]
Monadic bind satisfies ma >>= k = join (fmap k ma)
where ma :: m a, k :: a -> m b
for a Monad m
. Thus for lists, where fmap = map
, we have ma >>= k = join (fmap k ma) = concat (map k ma) = concatMap k ma
:
m >>= k = [ a, = join [ k a, = join [ [ a1, a2, ... ], = [ a1, a2, ... ,
b, k b, [ b1, b2, ... ], b1, b2, ... ,
c, k c, [ c1, c2, ... ], c1, c2, ... ,
d, k d, [ d1, d2, ... ], d1, d2, ... ,
e, k e, [ e1, e2, ... ], e1, e2, ... ,
... ] >>= k ... ] ............... ] ........... ]
which is exactly what nested loops do. Thus
pairs ["a", -- for x in ["a", "b"] do:
"b"] [2, 3] -- for y in [2, 3] do:
= -- yield (x,y)
["a",
"b"] >>= (\x-> join (fmap (\y -> return (x,y)) [2, 3]) )
=
["a",
"b"] >>= (\x-> concat (map (\y -> [ (x,y) ]) [2, 3]) )
=
join [ "a" & (\x-> concat ((\y -> [ (x,y) ]) `map` [2, 3]) ), -- x & f = f x
"b" & (\x-> concat ((\y -> [ (x,y) ]) `map` [2, 3]) ) ]
=
join [ concat ((\y -> [ ("a",y) ]) `map` [2, 3]) ,
concat ((\y -> [ ("b",y) ]) `map` [2, 3]) ]
=
join [ concat [ [("a", 2)], [("a", 3)] ] , -- for y in [2, 3] do: yield ("a",y)
concat [ [("b", 2)], [("b", 3)] ] ] -- for y in [2, 3] do: yield ("b",y)
=
join [ [ ("a", 2) , ("a", 3) ] ,
[ ("b", 2) , ("b", 3) ] ]
=
[ ("a", 2) , ("a", 3) ,
("b", 2) , ("b", 3) ]
Loop unrolling is what nested loops do ⁄ are, and nested computations are the essence of Monad.
It is also interesting to notice that
join = = [a1] ++ = [a1] ++ join
[ [ a1, a2, ... ], [ a1, a2, ... ] ++ [a2, ... ] ++ [ [a2, ...],
[ b1, b2, ... ], [ b1, b2, ... ] ++ [ b1, b2, ... ] ++ [ b1, b2, ...],
[ c1, c2, ... ], [ c1, c2, ... ] ++ [ c1, c2, ... ] ++ [ c1, c2, ...],
[ d1, d2, ... ], [ d1, d2, ... ] ++ [ d1, d2, ... ] ++ [ d1, d2, ...],
[ e1, e2, ... ], [ e1, e2, ... ] ++ [ e1, e2, ... ] ++ [ e1, e2, ...],
............... ] ............... ............... .............. ]
which goes to the heart of the "nested loops ⁄ yield" analogy. Monads are higher order monoids, "what's the problem?"
Upvotes: 2
Reputation: 476740
Let us first analyze and rewrite the function pairs
:
pairs a b = do { x <- a; y <- b; return (x, y)}
Here we thus have a monad. We use do
as syntactical sugar. But the compiler rewrites this to:
pairs a b = a >>= (\x -> b >>= (\y -> return (x, y)))
Or in a more canonical form:
pairs a b = (>>=) a (\x -> (>>=) b (\y -> return (x, y)))
Now the list monad is defined as:
instance Monad [] where
return x = [x]
(>>=) xs f = concatMap f xs
So we have written:
pairs a b = concatMap (\x -> concatMap (\y -> [(x, y)]) b) a
So we thus take as input two lists a
and b
, and we perform a concatMap
on a
with as function (\x -> concatMap (\y -> [(x, y)]) b)
. In that function we perform another concatMap
on b
with as function \y -> [(x, y)]
.
So if we evaluate this with pairs ["a", "b"] [2,3]
we get:
pairs ["a", "b"] [2,3]
-> concatMap (\x -> concatMap (\y -> [(x, y)]) [2,3]) ["a", "b"]
-> concatMap (\y -> [("a", y)]) [2,3] ++ concatMap (\y -> [("b", y)]) [2,3]
-> [("a", 2)] ++ [("a", 3)] ++ [("b", 2)] ++ [("b", 3)]
-> [("a", 2), ("a", 3), ("b", 2), ("b", 3)]
Upvotes: 5